Regional-based strategies for municipality carbon mitigation: A case study of Chongqing in China - Min Tang; Zhaoqi Zhang; Ying Liu; Hongwu Zhang (Energy Reports, 2022)
Different CO2carbon mitigation strategies are required due to the uneven development of regions. In China, the western region is rich in natural resources, but its industrial technology is not as advanced as other regions. In addition, a few studies have attempted to explore the CO2carbon mitigation strategies for a municipality of this region. In terms of modeling, the current studies often focus on the low-carbon potentials at the country, province, city and sector levels, while the carbon flows and their integration in neighboring regions are not well studied. In this paper, to explore the impact of regional-difference factors on CO2reduction, we propose regional-based CO2mitigation for a municipality and use Chongqing as a case study. In our methodology, the hierarchical structure analysis is conducted to identify the primary contradictions of regional CO2emissions. Then, using system dynamics, CO2emission systems of major industries, including cement, power and transportation, are modeled. Through simulations of baseline and low-carbon scenarios, key influencing factors in each industry are analyzed. They are then generalized to identify the important aspects of CO2emission reduction for this region. Finally, the low-carbon development strategy covering three sub-pathways, i.e., the industrial system, energy structure and socio development is discussed to help the local government for policy-making.